EFEKTIFITAS PENEGAKAN HUKUM TINDAK PIDANA RINGAN DI KOTA BATAM - Tantimin, Tantimin; Febriyani, Emiliya; Pertiwi, Putri Nada (Universitas Muhammadiyah Ponorogo, 2024)
The effectiveness of law enforcement is a crucial aspect in analyzing the performance of a country's legal system. The level of success in preventing law violations and creating a deterrent effect for potential criminals can be used as an indicator of effectiveness, both through existing legal theory and empirical approaches to law enforcement for minor crimes in accordance with applicable laws. The aim of this research is to identify the effectiveness of law enforcement against minor crimes in Batam City. The research method applied is the Empirical Legal Method, with data collection carried out through in-depth interviews with law enforcement officials, and researchers who are the key instruments for analyzing data accurately. The results of this research indicate that law enforcement against minor crimes in Batam City is in accordance with applicable operational standards. Analysis through interview data and a legal effectiveness theory approach shows that law enforcement against minor crimes in Batam City can be considered effective. These findings provide a clear picture of the achievement of law enforcement standards and their effectiveness, in accordance with relevant legal aspects.